Response Surface Optimization of Rotenone Using Natural Alcohol-Based Deep Eutectic Solvent as Additive in the Extraction Medium Cocktail. (11th January 2017) - Othman, Zetty Shafiqa; Hassan, Nur Hasyareeda; Zubairi, Saiful Irwan
Abstract : Rotenone is a biopesticide with an amazing effect on aquatic life and insect pests. In Asia, it can be isolated from Derris species roots ( Derris elliptica and Derris malaccensis ). The previous study revealed the comparable efficiency of alcohol-based deep eutectic solvent (DES) in extracting a high yield of rotenone (isoflavonoid) to binary ionic liquid solvent system ([BMIM]OTf) and organic solvent (acetone). Therefore, this study intends to analyze the optimum parameters (solvent ratio, extraction time, and agitation rate) in extracting the highest yield of rotenone extract at a much lower cost and in a more environmental friendly method by using response surface methodology (RSM) based on central composite rotatable design (CCRD). By using RSM, linear polynomial equations were obtained for predicting the concentration and yield of rotenone extracted. The verification experiment confirmed the validity of both of the predicted models. The results revealed that the optimum conditions for solvent ratio, extraction time, and agitation rate were 2 : 8 (DES : acetonitrile), 19.34 hours, and 199.32 rpm, respectively. At the optimum condition of the rotenone extraction process using DES binary solvent system, this resulted in a 3.5-fold increase in a rotenone concentration of 0.49 ± 0.07 mg/ml and yield of 0.35 ± 0.06 (%, w/w) as compared to the control extract (acetonitrile only). In fact, the rotenone concentration and yield were significantly influenced by binary solvent ratio and extraction time (P < 0.05 ) but not by means of agitation rate. For that reason, the optimal extraction condition using alcohol-based deep eutectic solvent (DES) as a green additive in the extraction medium cocktail has increased the potential of enhancing the rotenone concentration and yield extracted.